2014
DOI: 10.1002/lt.23786
|View full text |Cite
|
Sign up to set email alerts
|

Prerecovery liver biopsy in the brain-dead donor: A case-control study of logistics, safety, precision, and utility

Abstract: Prerecovery liver biopsy (PLB) can potentially to decrease futile recovery and increase utilization of marginal brain-dead donor (BDD) livers. A case-control study was conducted to examine the logistics, safety, histological precision, and liver utilization associated with PLB in BDDs. Twenty-three cases between January 2008 and January 2013 were compared to 2 groups: 48 sequential and 69 clinically matched controls. Compared to the sequential controls, the cases were older (53 versus 46 years), heavier (30.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 33 publications
5
9
0
Order By: Relevance
“…These reports represent the largest study of rates of graft biopsy with variability in graft utilization seeming to be largely transplant center and OPO dependent . With regard to outcome, Oliver et al have demonstrated that liver biopsy is safe in deceased donors and our data expand upon their work to show that there are no long‐term adverse effects of procurement biopsy on patient or graft survival …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…These reports represent the largest study of rates of graft biopsy with variability in graft utilization seeming to be largely transplant center and OPO dependent . With regard to outcome, Oliver et al have demonstrated that liver biopsy is safe in deceased donors and our data expand upon their work to show that there are no long‐term adverse effects of procurement biopsy on patient or graft survival …”
Section: Discussionsupporting
confidence: 56%
“…Liver biopsy has been demonstrated to be a method of identifying occult liver disease which may be indiscernible from clinical parameters alone . Additionally, the use of pre‐recovery liver biopsies has been shown to decrease futile liver recovery, though it has been suggested that this practice may also lead to exclusion of livers that might have been deemed useable at time of recovery, for the appropriate recipient . The determination of which donors require a biopsy and the impact of biopsy findings remains surgeon and transplant center dependent …”
Section: Introductionmentioning
confidence: 99%
“…Despite the use of PLB in brain death donors in many OPOs in the United States, the existing literature on this topic is sparse. Our large study provides substantially more information on the important issues of safety, futile liver recovery, and liver utilization than the existing 3 single‐center–based publications . The multifaceted diversity in the OPOs and their donor population allow for greater generalizability of our findings.…”
Section: Discussionmentioning
confidence: 85%
“…That is in contrast to an almost 30% rate of intraoperative biopsy . Evidence from 3 single OPO studies suggests that PLB decreases futile liver recovery and may be cost‐effective, particularly in liver‐only donors . There are no large studies confirming this and the safety of PLB.…”
mentioning
confidence: 97%
“…Liver biopsy before organ recovery has been demonstrated to be "logistically feasible" for decreasing futile organ retrieval. 9 This method has significantly decreased the proportion of attempted liver recoveries that did not end in transplant (from 31.9% to 8.7%; P = .009).…”
Section: Introductionmentioning
confidence: 91%